2003
DOI: 10.3122/jabfm.16.5.399
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exit-Interview Patient Education on No-Show Rates at a Family Practice Residency Clinic

Abstract: Background: Residency clinics with high no-show rates experience negative ramifications in patient health care, continuity, clinic productivity, and learning experiences for residents. This study tested patient education in the form of an exit interview to reduce no-show rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Literature from other medical specialties to improve clinic visits has demonstrated that exit-interviews can improve patient adherence with clinic visits. 13 Exit-interviews consisted of asking patients if their questions and concerns were addressed, if they understood the information received, and if they agreed with the course of treatment. The education stage of our project did not include any of these components, which may have diminished the impact of the education stage of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Literature from other medical specialties to improve clinic visits has demonstrated that exit-interviews can improve patient adherence with clinic visits. 13 Exit-interviews consisted of asking patients if their questions and concerns were addressed, if they understood the information received, and if they agreed with the course of treatment. The education stage of our project did not include any of these components, which may have diminished the impact of the education stage of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' understanding can be increased with a simple discharge or exit interview explaining the need for follow-up and the rationale for medication. This approach appears to reduce subsequent nonattendance (Guse et al, 2003). Given that one of the most important interpersonal variables in predicting attendance is the degree of helpfulness of the health professional (see above) we suggest that all clinicians check whether there is anything further that can be done to help at the close of all appointments and prior to hospital discharge.…”
Section: Interpersonal and Communication Issuesmentioning
confidence: 99%
“…Stressing the importance of educator appointm e n t s m a y r e d u c e s h o r t -n o t i c e cancellations. Guse et al (24) found that providing patients with exit interviews or debriefings after appointments improved attendance at subsequent visits, while others found mailing detailed information about upcoming appointments and following up with a phone call improved attendance (25). Thus, providing patients with information that explains why attendance at appointments is important to their health may help improve attendance.…”
mentioning
confidence: 99%